Deactivating Emission in Azulene via Solvent-Induced (Anti)Aromaticity - Kiser Z. Colley; Shilpa Debnath; Ulrike Salzner; Satish Patil; Andrew J. Musser (Journal of the American Chemical Society, 2026)
Abstract Anti-Kasha emission is a coveted feature in optoelectronics, with promise in areas such as imaging, sensing, and the production of white-light LEDs via dual-photon emission. Despite being a rare feature in organic systems, anti-Kasha emission is readily observed in the deceptively simple molecule azulene, which possesses two bright singlet states in the UV–visible spectrum and readily emits from the S2 state. With dominant anti-Kasha emission and decades of synthetic study, azulene is a perfect candidate for novel material fabrication; however, large gaps persist in understanding the photophysics of even the simple parent compound. These range from competing, experimentally unverified models of azulene reactivity and aromaticity to the unexplained deactivation of anti-Kasha emission in a host of azulene derivatives. Herein, we use fluorescence and transient absorption spectroscopies to explore the detailed solvent dependence of azulene photophysics. We discover a tunable reduction in the S2 lifetime via weak complexation with aromatic solvents. Interestingly, our results are independent of polarity, highlighting the primacy of peripherally delocalized 10-π Hückel aromaticity over zwitterionic character. When the dipolar character is enhanced through chemical functionalization, we observe even greater sensitivity to solvent aromaticity and more rapid quenching, revealing the role of conical intersections in azulenes with zwitterionic excited states. Overall, this work provides essential mechanistic insight into the photophysics of azulene and reveals a simple new approach to control the excited-state aromaticity and anti-Kasha emission in this class of materials.